2022
DOI: 10.1093/intimm/dxac044
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 ORF8 is a viral cytokine regulating immune responses

Abstract: Many patients with severe COVID-19 suffer from pneumonia and the elucidation of the mechanisms underlying the development of this severe condition is important. The in vivo function of the ORF8 protein secreted by SARS-CoV-2 is not well understood. Here, we analyzed the function of ORF8 protein by generating ORF8-knockout SARS-CoV-2 and found that the lung inflammation observed in wild-type SARS-CoV-2-infected hamsters was decreased in ORF8-knockout SARS-CoV-2-infected hamsters. Administration of recombinant O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…These data indicate that the intrinsic pathogenicity has lowered on evolution due to the acquisition of the S:S486P and ORF8 stop mutations. In a previous study, Kohyama et al showed that ORF8 functions as a viral cytokine and that functional loss of ORF8 resulted in impairment of inflammation 30 . As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that the intrinsic pathogenicity has lowered on evolution due to the acquisition of the S:S486P and ORF8 stop mutations. In a previous study, Kohyama et al showed that ORF8 functions as a viral cytokine and that functional loss of ORF8 resulted in impairment of inflammation 30 . As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several groups have revealed that ∆ORF8 SARS-CoV-2 had reduced replication capabilities in immune-competent human pulmonary cells, particularly in angiotensinconverting enzyme 2 (ACE2)-expressing A549 (hACE2-A549) cells and in induced human pluripotent stem cell-derived lung alveolar type II (iAT2) cells, and it generated fewer and less infectious viral particles than wild-type SARS-CoV-2 in viral plaque assays [58][59][60]. Consistent with findings in COVID-19 patients, Syrian hamsters infected with ∆ORF8 SARS-CoV-2 experienced milder disease, with reduced immune infiltration, lung damage, and inflammatory cytokine production compared to wild-type, despite no significant effect on viral titer [61]. Detailed studies in K18-human ACE2 transgenic mice did not show a significant impact of ORF8-deletions on SARS-CoV-2 morbidity, mortality, viral lung titers, inflammation, and tissue damage [58,60].…”
Section: Orf8 Evolution During the Covid-19 Pandemicmentioning
confidence: 59%
“…ORF8 interaction with IL-17RA is implicated in ORF8 binding to monocytes in human blood, as well as to both THP1 and U937 monocytic cell lines [35,36,41,46,61]. Concordantly with the fact that monocytes are major drivers of the atypical cytokine storm contributing to severe COVID-19, ORF8-treatment of either CD14+/CD16+ monocytes or THP1 cells also results in pro-inflammatory cytokine overexpression (Figure 3) [35,36,46,61,91,92]. Ongoing work reveals that ORF8-monocyte interactions may not influence the differentiation of these cells into dendritic cells (DCs), but rather promote DC maturation and resulting cytokine storm [41].…”
Section: Orf8 As a Virokinementioning
confidence: 99%
“…Recently, several groups have independently reported that ORF8 is a secretory protein [ 34 , 52 – 55 ]; however, some of the results seem inconsistent with the others. For example, we found that the unglycosylated form of ORF8 was relatively low in Matsuoka’s system [ 52 ], while in our system 34.5~46.1% of ORF8 ( Fig 3B ) was unglycosylated.…”
Section: Discussionmentioning
confidence: 99%